High Neutrophil-to-Lymphocyte Ratio Is an Early Predictor of Bronchopulmonary Dysplasia - Sun, Yuanyuan; Chen, Cuie; Zhang, Xixi; Weng, Xiaocai; Sheng, Anqun; Zhu, Yanke; Chen, Shujun; Zheng, Xiexia; Lu, Chaosheng (Frontiers in Pediatrics, 2019)
Background and Objective: Bronchopulmonary dysplasia (BPD) is a common complication in preterm infants; predicting the degree of BPD at an early life stage is difficult. Inflammation is a crucial risk factor for BPD pathogenesis, and the neutrophil-to-lymphocyte ratio (NLR) is a potential systemic inflammatory biomarker. We aimed to assess the predictive value of the NLR for BPD. Methods: We carried out a retrospective, single-center, observational study of neonates with gestational ages (GAs) <32 weeks and assessed the association between the NLR and BPD. Results: The study population included 296 preterm infants with BPD (n = 144) or without BPD (n = 152). Among the infants, 75 (25.3%) had mild BPD, 37 (12.5%) had moderate BPD, and 32 (10.8%) had severe BPD. The BPD group had a higher NLR at birth and at 72 h than the non-BPD group. The NLR cutoff value at 72 h for the prediction of BPD was 3.035 (sensitivity = 0.519, specificity = 0.964), and the area under the curve (AUC) was 0.714. The NLR cutoff value at 72 h for predicting severe BPD was 3.105 (sensitivity =0.607, specificity = 0.819), with an AUC of 0.756. At the NLR cutoff value at 72 for the prediction of BPD, the AUCs were 0.640 and 0.970 in the preterm infants with EOS and congenital pneumonia, respectively. Conclusions: The NLR is an inexpensive, accessible and convenient tool; an increase in the NLR at 72 h could be an early predictor of BPD, especially severe BPD. Additionally, the NLR at 72 h could be a predictor of BPD in preterm infants with intrauterine infections.